Properties of hybrid particleboard from acacia mangium and oil palm trunk / Wan Jamalludin Wan Omar, Jamaludin Kasim and Zaimatul Aqmar Abdullah - Wan Omar, Wan Jamalludin; Kasim, Jamaludin; Abdullah, Zaimatul Aqmar (2015)
The purpose of this study is to evaluate the effects resin content and wood ratio on the properties of hybrid particleboard made from Acacia and Oil Palm Trunk (OPT). This study used Acacia (100%), Acacia + OPT (50%:50%) and OPT (100%). The middle part from both species was used and the target density was fixed at 650kg/m3. Twenty seven boards were produced and tested for physical and mechanical properties based on the European Standard (EN). The resin contents of board were 7%,9% and 11% and phenol formaldehyde resin (PF) was used. On the mechanical properties, from of the three wood ratio, 100% Acacia showed the highest value for modulus of rupture for 11% resin content with 15.19 MPa and the lowest value is from wood ratio 100% OPT, 7% resin content with 3.7 MPa. Meanwhile, the best value for modulus of elasticity test results was from wood ratio 100% Acacia with 11% resin content at value of 2426.96 MPa. Then, internal bond result showed that the highest value is from wood ratio 100% Acacia (11% resin content) with value 0.49 MPa and the lowest value wood ratio 100% OPT (both 7% and 9% resin content) with value 0.05 MPa. On the physical properties, the best value of thickness swelling comes from wood ratio 100% OPT (11% resin content) with value 7.98% and the least value from wood ratio 100% Acacia (7% resin content) with value 13.89%. For water absorption 100% Acacia (9% resin content) with 62.24% gave the best performance while the least value is from 100% OPT (7% resin content) with 81.38%. The entire sample from mechanical properties did not achieve the standard requirements.